2006
DOI: 10.2460/ajvr.67.9.1541
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of an oscillometric blood pressure monitor during phenylephrine-induced hypertension in dogs

Abstract: In normotensive dogs, oscillometric measurements of MAP and SAP agreed more closely with direct arterial pressure measurements than oscillometric estimates of DAP. Oscillometric measurement of MAP was accurate during both normotension and hypertension in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
3
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 13 publications
7
48
3
5
Order By: Relevance
“…To reduce stress, we paid particular attention to restraining the lambs gently for at least 5 min before taking the blood pressure measurement. In general, the indirect oscillometric measurement of mean arterial blood pressure has been shown to agree closely with direct arterial pressure measurements during both normotension and hypertension in dogs [35,36], and we confirmed this agreement in our own experiments on anesthetized sheep. Direct measurement is generally considered to be more suitable for detecting subtle differences and could have resulted in lower standard deviations and a more accurate determination of blood pressure.…”
Section: Discussionsupporting
confidence: 85%
“…To reduce stress, we paid particular attention to restraining the lambs gently for at least 5 min before taking the blood pressure measurement. In general, the indirect oscillometric measurement of mean arterial blood pressure has been shown to agree closely with direct arterial pressure measurements during both normotension and hypertension in dogs [35,36], and we confirmed this agreement in our own experiments on anesthetized sheep. Direct measurement is generally considered to be more suitable for detecting subtle differences and could have resulted in lower standard deviations and a more accurate determination of blood pressure.…”
Section: Discussionsupporting
confidence: 85%
“…Cuff site variably affects BP measurement in different species, with no differences reported between forelimb and hind limb cuff placement in dogs (McMurphy et al, 2006), whereas significant differences were found between different locations in marmosets (Mietsch and Einspanier, 2015), rabbits (Ypsilantis et al, 2005) and cats (Binns et al, 1995). Similar to the studies in cats and rabbits, cuff site influences accuracy of BP measurement in ferrets, with hind limb measurements displaying higher bias, wider limits of agreement and lower correlation coefficients than forelimb and tail measurements.…”
Section: Discussionsupporting
confidence: 53%
“…Hence they actually assess the agreement between two different measurement techniques rather than the accuracy of the new technique (Mantha et al 2000). No such standards exist in veterinary medicine, however many recent papers utilize the human accuracy standards but do not appear to adopt the standard methodologies (Binns et al 1995;Branson et al 1997;Pedersen et al 2002;Sawyer et al 2004;Giguère et al 2005;McMurphy et al 2006;Valerio et al 2006;Deflandre and Hellebrekers 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Two non-invasive blood pressure techniques are commonly used in veterinary anaesthesia, automatic oscillometric monitors and manual Doppler monitors. Many studies have compared oscillometric techniques with invasive methods for measuring blood pressure in dogs whilst conscious and anaesthetised with variable results (Geddes et al 1980;Gains et al 1995;Sawyer et al 2004;McMurphy et al 2006;Valerio et al 2006;Deflandre and Hellebrekers 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation